Quantitative evidence of goodwin’s non-linear growth cycles (2010)
The article searches for quantitative evidence in favor of an extended version of Goodwin´s predator-prey model of endogenous distribution-employment cycles for 16 countries. The model is extended to include several harmonics in both series. The model fits all the observations both within sample and out of sample for half of the countries, with a 10% error, and for 4 countries with a 5% error. This suggests that the model may be useful in empirical work.